2023
DOI: 10.3390/jcm12051919
|View full text |Cite
|
Sign up to set email alerts
|

“What Did I Tell This Sad Person?”: Memory for Emotional Destinations in Korsakoff’s Syndrome

Abstract: We investigated destination memory, defined as the ability to remember to whom a piece of information was previously transmitted, for emotional destinations (i.e., a happy or sad person) in Korsakoff’s syndrome (KS). We asked patients with KS and control participants to tell facts to neutral, positive, or negative faces. On a subsequent recognition task, participants had to decide to whom they told each fact. Compared with control participants, patients with KS demonstrated lower recognition of neutral, emotio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…Compared with other memory systems (e.g., episodic memory, working memory), destination memory is essentially oriented toward social interactions [ 9 , 10 , 11 , 13 , 14 , 17 , 19 , 23 ]. Supporting this assumption, research has demonstrated how destination memory can vary following the familiarity of interlocutors [ 43 ] or their age [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with other memory systems (e.g., episodic memory, working memory), destination memory is essentially oriented toward social interactions [ 9 , 10 , 11 , 13 , 14 , 17 , 19 , 23 ]. Supporting this assumption, research has demonstrated how destination memory can vary following the familiarity of interlocutors [ 43 ] or their age [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Impairments in social cognition in TBI have also been reported by research on destination memory. Destination memory refers to the ability to remember to whom a piece of information was previously transmitted [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. Research has demonstrated a decline in destination memory in TBI, which was found to be related to the ability to represent, conceptualize, and reason about others’ mental states [ 11 , 18 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation